2019
DOI: 10.11616/basbed.v19i47045.514607
|View full text |Cite
|
Sign up to set email alerts
|

Yurtdişi Yerleşi̇kleri̇ni̇n Hi̇sse Senedi̇ Yatirimlarinin Borsa İstanbul’a Etki̇si̇

Abstract: Bu çalışmada, yurtdışı yerleşiklerin hisse senedi yatırımlarının BİST100 endeksi ile ilişkisi araştırılmıştır. Çalışmada 01.01.2010-23.02.2018 dönemlerine ait haftalık veriler yardımıyla değişkenler arasındaki eşbütünleşme ve nedensellik ilişkisi Johansen eşbütünleşme ve Granger nedensellik testleriyle incelenmiştir. Sonuç olarak; değişkenler arasında uzun dönemde anlamlı bir ilişkinin bulunduğu ve yurtdışı yerleşiklerin hisse senedi yatırımlarından BIST100'e doğru tek yönlü nedensellik olduğu tespit edilmişti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
3
1
1
Order By: Relevance
“…The findings of bidirectional causality are consistent with the empirical results presented in the literature by Köycü & Ege (2023) and Şit et al (2020). However, the bidirectional causality finding contradicts the results of Hamurcu (2021) and Polat & ve Kılıç (2019), who found a unidirectional causality in similar studies. The divergence of findings might be attributed to variations in the data frequency used in the analysis (weekly, monthly, quarterly) and to differences in the time intervals adopted in the studies.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…The findings of bidirectional causality are consistent with the empirical results presented in the literature by Köycü & Ege (2023) and Şit et al (2020). However, the bidirectional causality finding contradicts the results of Hamurcu (2021) and Polat & ve Kılıç (2019), who found a unidirectional causality in similar studies. The divergence of findings might be attributed to variations in the data frequency used in the analysis (weekly, monthly, quarterly) and to differences in the time intervals adopted in the studies.…”
Section: Discussioncontrasting
confidence: 89%
“…A 1% increase in foreign purchases resulted in a 15.58% increase in the BIST 100 index, while a 1% increase in foreign sales led to a 16.43% decrease in the BIST 100 index. Polat & ve Kılıç (2019) examined the relationship between equity investments by non-residents and the BIST100 index for the period 2010-2018. In their study, they identified a significant long-term relationship between the variables and concluded that there is a unidirectional causality from equity investments to the BIST100 index.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…sıcak paranın, BIST100 endeksi kapanış fiyatı, faiz oranı ve döviz kuru üzerindeki etkisini analiz etmişlerdir. Analiz sonuçlarında, sıcak paranın bu üç makro değişken üzerindeki etkisi anlamlı bulunmuştur Polat ve Kılıç (2019),. yurtdışındaki yatırımcıların hisse senetlerine yaptıkları yatırımlarının BIST100 ile ilişkisini araştırmışlardır.…”
unclassified